Human monkeypox disease (MPX) - Farahat, Ramadan Abdelmoez (2022)
Monkeypox is a rare viral infection, endemic in many central and western African countries. The last international outbreak of monkeypox reported outside Africa occurred back in 2003. However, monkeypox has reemerged at a global scale with numerous confirmed cases across the globe in 2022. The rapid spread of cases through different countries has raised serious concerns among public health officials worldwide prompting accelerated investigations aimed to identify the origins and cause of the rapid expansion of cases. The current situation is reminiscent of the very early stages of the still ongoing COVID-19 pandemic. Overlapping features between these, two seemingly alike viral entities include the possibility for airborne transmission and the currently unexplained and rapid spread across borders. Early recognition of cases and timely intervention of potential transmission chains are necessary to contain further outbreaks. Measures should include rapid and accurate diagnosis of cases meeting case definitions, active surveillance efforts, and appropriate containment of confirmed cases. Governments and health policymakers must apply lessons learned from previous outbreaks and start taking active steps toward limiting the recent global spread of monkeypox. Herein, we discuss the status of the current monkeypox outbreaks worldwide, the epidemio-logical and public health situation at a global scale and what can be done to keep at bay its further expansion and future global implications.